Kualitas Pelayanan Pengujian Kendaraan Bermotor Pada Dinas Perhubungan Kota Yogyakarta - Khairunnisa Khairunnisa (Universitas Muhammadiyah Mataram, 2022)
The purpose of this research was to service quality of Vehicle Inspection in Transportation Agency of Yogyakarta as well as it’s supporting and hampering factors. The research design used qualitative approach with descriptive method. The data were collected through interviews, observation, and documentation. The data validation were done through source triangulation and the data were analyzed using Miles and Huberman’s analysis model. The results of the research showed that the service quality of Vehicle Inspection in Transportation Agency of Yogyakarta was already good, it can be seen from tangibility, reliability, responsiveness, assurance, and empathy. However, there were still hampering factors in the improvement of the service quality such as the system that is not yet integrated to the Ministry of Transportation’s information system, the lack of people’s awareness to take periodical vehicle inspection, the socialization about vehicle inspection that is not directly done by the Technical Implementation Unit of Vehicle Inspection, the unavailability of online registration, and the absence of installation service of certificate as well as plate of periodical vehicle inspection.